2010
DOI: 10.1590/s0036-46652010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Melanoides tuberculata (Mollusca: Thiaridae) as an intermediate host of Centrocestus formosanus (Trematoda: Heterophyidae) in Brazil

Abstract: SUMMARYPleurolophocercous cercariae emerged from naturally infected Melanoides tuberculata from Minas Gerais State, Brazil, were used to perform experimental infection of laboratory-reared Poecilia reticulata. Mature metacercariae were obtained from the gills of fishes and force-fed to Mus musculus. The adult parasites which recovered from small intestines of mice were identified as Centrocestus formosanus. This is the first report of M. tuberculata as intermediate host of this heterophyid in Brazil. Despite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 26 publications
(29 reference statements)
2
33
0
6
Order By: Relevance
“…Haplorchis taichui, Haplorchis pumilio, Stellantchasmus falcatus, Centrocestus caninus and Procerovum sp. were reported to be as the cercarial stage of the intestinal trematode in family Heterophyidae [18][19][20][21][22][23][24][25] . The identification of the morphology of cercariae were similar to those described by previous reported [8,16,20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplorchis taichui, Haplorchis pumilio, Stellantchasmus falcatus, Centrocestus caninus and Procerovum sp. were reported to be as the cercarial stage of the intestinal trematode in family Heterophyidae [18][19][20][21][22][23][24][25] . The identification of the morphology of cercariae were similar to those described by previous reported [8,16,20] .…”
Section: Discussionmentioning
confidence: 99%
“…were reported to be as the cercarial stage of the intestinal trematode in family Heterophyidae [18][19][20][21][22][23][24][25] . The identification of the morphology of cercariae were similar to those described by previous reported [8,16,20] . In regard to this connection, previous surveys revealed that most metacercariae found in Mae Taeng district, Chiang Mai province belonged to the family Heterophyidae [3,6,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five adult parasites were recovered from the small intestine of the mice 15 days after infection. The morphological analysis of the developmental stages (cercariae, metacercariae and adult parasites) was performed as described in Pinto and Melo (2010a); this confirmed the presence of C. formosanus in M. tuberculata from Paranoá Lake. The studied snails and adult trematodes obtained in this study were deposited respectively in the collections of the Departments of Zoology (2688-2689 and 2692-2696) and Parasitology (5923a-d) at the Universidade Federal de Minas Gerais.…”
mentioning
confidence: 79%
“…This is an artificial reservoir that was constructed in 1959 to provide recreational activities in Brasília (Monteiro and Dias, 1980;PadovesiFonseca et al, 2009). All procedures, such as collecting thiarids, detecting larval trematode, the experimental infection of fish Poecilia reticulata (Peters, 1859), the infection of mice (AKR/J strain), metacercariae recovery, and the fixation and colouration of the obtained parasites were performed as described by Pinto and Melo (2010a). Trematode larvae were found in 16 snails (33%) and were preliminarily identified as Pleurolophocercous cercariae.…”
mentioning
confidence: 99%
See 1 more Smart Citation